Regional, household and individual factors that influence soil transmitted helminth reinfection dynamics in preschool children from rural indigenous Panamá. - Carli M Halpenny (Public Library of Science (PLoS), 2013)
Background Few studies have investigated the relative influence of individual susceptibility versus household exposure factors versus regional clustering of infection on soil transmitted helminth (STH) transmission. The present study examined reinfection dynamics and spatial clustering of Ascaris lumbricoides, Trichuris trichiura and hookworm in an extremely impoverished indigenous setting in rural Panamá over a 16 month period that included two treatment and reinfection cycles in preschool children. Methodology/principle findings Spatial cluster analyses were used to identify high prevalence clusters for each nematode. Multivariate models were then used (1) to identify factors that differentiated households within and outside the cluster, and (2) to examine the relative contribution of regional (presence in a high prevalence cluster), household (household density, asset-based household wealth, household crowding, maternal education) and individual (age, sex, pre-treatment eggs per gram (epg) feces, height-for-age, latrine use) factors on preschool child reinfection epgs for each STH. High prevalence spatial clusters were detected for Trichuris and hookworm but not for Ascaris. These clusters were characterized by low household density and low household wealth indices (HWI). Reinfection epg of both hookworm and Ascaris was positively associated with pre-treatment epg and was higher in stunted children. Additional individual (latrine use) as well as household variables (HWI, maternal education) entered the reinfection models for Ascaris but not for hookworm. Conclusions/significance Even within the context of extreme poverty in this remote rural setting, the distinct transmission patterns for hookworm, Trichuris and Ascaris highlight the need for multi-pronged intervention strategies. In addition to poverty reduction, improved sanitation and attention to chronic malnutrition will be key to reducing Ascaris and hookworm transmission.